2015
DOI: 10.2147/nds.s52022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamins C and D in type 2 diabetes mellitus

Abstract: Scurvy and rickets are largely considered historical diseases in developed countries. However, deficiencies in vitamins C and D are re-emerging due to increased consumption of processed foods and reduced fresh foods in the Western diet, as well as to an indoor sedentary lifestyle away from sun exposure. These dietary and lifestyle factors also predispose one to diabetes and metabolic syndrome. Our understanding of the potential roles of vitamin C (an antioxidant) and vitamin D (a biologically active hormone) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 75 publications
(79 reference statements)
2
18
0
Order By: Relevance
“…Although we had lost few patients to follow up, we were able to achieve a target sample size throughout the course of the study. The significant reduction in fasting blood glucose levels (Table 2) agrees with the report published by Girgis C et al 2015 [7]. Similarly Kostisawat J et al had reported that Vitamin C might help in reduction of glycated haemoglobin levels in Diabetes patients [8].…”
Section: Discussionsupporting
confidence: 87%
“…Although we had lost few patients to follow up, we were able to achieve a target sample size throughout the course of the study. The significant reduction in fasting blood glucose levels (Table 2) agrees with the report published by Girgis C et al 2015 [7]. Similarly Kostisawat J et al had reported that Vitamin C might help in reduction of glycated haemoglobin levels in Diabetes patients [8].…”
Section: Discussionsupporting
confidence: 87%
“…Little is known about the effects of vitamin C in prediabetes, especially because controlled DM2-prevention studies using vitamin C are still needed 32 . In the present study, both groups given vitamin C had significantly lower fasting glycemia than the control group, demonstrating a glycemia-lowering effect of the vitamin.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of vitamin C have been suggested as a plausible mechanism for the reduced risk of T2DM with high vitamin C intakes or plasma concentrations (6,7) . However, a review of observational studies indicated that these associations were evident in some but not in all previous studies (8) . Moreover, no association was reported in a large randomised controlled trial (9) .…”
mentioning
confidence: 92%